2001
DOI: 10.1046/j.1526-0968.2001.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Powdered Sorbent Liver Dialysis and Pheresis in Treatment of Hepatic Failure

Abstract: The Liver Dialysis Unit (the Unit) is a liver‐assist device that employs hemodiabsorption (dialysis of blood against powdered sorbents) to selectively remove numerous small molecular weight toxins of hepatic failure. The Unit has been cleared by the Food and Drug Administration and is indicated and marketed for treatment of acute hepatic encephalopathy (AHE) due to decompensation of chronic liver disease (A‐on‐C) or fulminant hepatic failure (FHF). Controlled, prospective, and randomized studies of liver dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…A method for immobilising the powdered charcoal in a block is being evaluated for increased toxin binding capacity and better regeneration of dialysate 14 15. The next system should be able to support any type of hollow fibre (TUs 1 to 4).…”
Section: Liver Support For Patients With Liver Failure: State Of the Artmentioning
confidence: 99%
“…A method for immobilising the powdered charcoal in a block is being evaluated for increased toxin binding capacity and better regeneration of dialysate 14 15. The next system should be able to support any type of hollow fibre (TUs 1 to 4).…”
Section: Liver Support For Patients With Liver Failure: State Of the Artmentioning
confidence: 99%
“…The elevated levels of circulating IL-6 and TNFα, also described by others[42,43], have been related to attempts at liver regeneration[44,45] and liver injury[46], respectively. Therapeutic approaches targeting the clearance of inflammatory/toxic products (plasmapheresis, hemodiafiltration, and bioartificial livers) from the liver or anti-cytokine therapy are currently being considered[42,47-49] despite contradictory clinical results[50,51]. …”
Section: Discussionmentioning
confidence: 99%
“…Experimental approaches have included hemodiabsorption 44 and the molecular adsorbent recirculating system (MARS). 45,46 Small studies using these techniques in the management of hepatic failure showed benefit in patients with acute-on-chronic hepatic failure, 44 the hepatorenal syndrome, 45 and even fulminant hepatic failure. 46 In the absence of more robust evidence to confirm these findings, however, no recommendation can be given to support their routine use in clinical practice.…”
Section: Liver Supportmentioning
confidence: 99%